Accelerating sustainability in fashion, clothing and textiles - Charter, Martin; Pan, Bernice; Black, Sandy (Abingdon, Oxon ; New York, NY : Routledge, 2024)
'The issue of sustainability is characterised as a'wicked problem' in the fashion, clothing and textiles sector and is now coming into increased focus due to growing consumer, business and policy pressures. This in-depth volume presents a comprehensive overview of the challenges and emerging opportunities faced by the sector, and provides strategic solutions as to how the sector can substantially accelerate sustainability. This book collates research and industry best practice to provide a'one-stop-shop' exploring the complex and interconnected issues surrounding sustainability in fashion, clothing and textiles. The practical and digestible chapters include innovative examples and perspectives from different regions of the globe, addressing topics from policies to supply chain issues and materials innovation. Five unique case studies of sustainable businesses provide detailed examples of pioneering practice. Edited by three editors with long-standing knowledge and expertise, the book takes a global perspective with examples that illustrate the scale and breadth of topics and regions in the scope of sustainability. This holistic approach brings together both academic and industry perspectives on the critical areas that require immediate action to move towards a more sustainable fashion, clothing and textile sector. This is an invaluable resource for those working in the industry, policymakers, and for those in business or academia with an interest in sustainability in fashion, clothing, textiles and related sectors worldwide. It is also relevant to professionals and students in the areas of sustainability, innovation, supply chains, design and development, consultancy, education and training'--
Includes bibliographical references and index.
Description based on print version record.
Keywords: Clothing trade -- Environmental aspects; Textile industry -- Environmental aspects; Fashion merchandising -- Environmental aspects